2015
DOI: 10.1007/s11695-015-1569-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Preoperative Weight Loss in Morbidly Obese Adults Waiting for Bariatric Surgery: A Prospective Cohort Study

Abstract: A relatively low proportion of patients lost the recommended weight preoperatively. Our results indicate that patients benefit from monitoring weight preoperatively and that allowing patients to keep their high weight loss goals may contribute to higher weight loss. Further investigation of these predictors could provide valuable knowledge regarding how to support and motivate patients to lose weight preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
6
0
2
Order By: Relevance
“…Of the remaining studies, 21 met the inclusion criteria. Following detailed assessment of the full manuscripts, five studies (2 reviews, 2 with no control groups and 1 with no relevant reported outcomes) were excluded. The remaining 16 publications included four RCTs and 12 cohort studies, of which four 33–35,37 were prospective and eight retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining studies, 21 met the inclusion criteria. Following detailed assessment of the full manuscripts, five studies (2 reviews, 2 with no control groups and 1 with no relevant reported outcomes) were excluded. The remaining 16 publications included four RCTs and 12 cohort studies, of which four 33–35,37 were prospective and eight retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have analysed preoperative predictors of WL after BS, detecting personality traits, cognitive function, mental health, and binge eating as negative factors (Agüera et al, 2015;García-Ruiz-de-Gordejuela et al, 2017;Wimmelmann, Dela, & Mortensen, 2014), only few studies have explored predictors of poor WL achievement prior to BS. Predictors for poor WL prior to BS include being female and non-Caucasian (Hutcheon, Byham-Gray, Marcus, Scott, & Miller, 2017), a high snacking frequency (Bergh, Lundin Kvalem, Risstad, & Sniehotta, 2016), the presence of depressive symptomatology (Nicolau et al, 2017), and having a number of comorbidities (Bergh, Kvalem, Risstad, Cameron, & Sniehotta, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The mean interval between indication for surgery and the procedure was long (over 2 years) and the patients experienced 5.7% total body weight loss during this period compared with basal weight or 17.58% of total body weight loss (TBWL). It has been demonstrated that the patients may benefit from close monitoring of weight preoperatively; therefore, our program performs periodic visits while on the wait list, on average one visit quarterly [8]. …”
Section: Discussionmentioning
confidence: 99%